2013
DOI: 10.1371/journal.pone.0054171
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Genetic Diversity in a Rapidly Expanding Population of the Greater Long-Tailed Hamster (Tscherskia triton) as Revealed by Microsatellites

Abstract: Genetic diversity is essential for persistence of animal populations over both the short- and long-term. Previous studies suggest that genetic diversity may decrease with population decline due to genetic drift or inbreeding of small populations. For oscillating populations, there are some studies on the relationship between population density and genetic diversity, but these studies were based on short-term observation or in low-density phases. Evidence from rapidly expanding populations is lacking. In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 36 publications
3
8
0
Order By: Relevance
“…As shown in Figure 2, an obvious correlation can be inferred between the levels of genetic diversity and the population density. Our results are in accordance with studies in other species in which a similar correlation was found (Aspi et al 2006;Berthier et al 2006;Eckert et al 2008;Frankham 1996;Furlan et al 2012;Montgomery et al 2000;Wang et al 2013), including other rodents (Krebs 2013) and hamster species (Romanenko et al 2007), like the greater longtailed hamster (Dong et al 2010;Xie and Zhang 2006;Xu et al 2013a;Xue et al 2014), the golden hamster (Karsten et al 2005), and the common hamster (Banaszek et al 2012;Neumann et al 2005). Similarly, the genetic diversity of the striped hamster has experienced a trend of continuous decline in recent years.…”
Section: Genetic Diversity and Genetic Differentiationsupporting
confidence: 92%
“…As shown in Figure 2, an obvious correlation can be inferred between the levels of genetic diversity and the population density. Our results are in accordance with studies in other species in which a similar correlation was found (Aspi et al 2006;Berthier et al 2006;Eckert et al 2008;Frankham 1996;Furlan et al 2012;Montgomery et al 2000;Wang et al 2013), including other rodents (Krebs 2013) and hamster species (Romanenko et al 2007), like the greater longtailed hamster (Dong et al 2010;Xie and Zhang 2006;Xu et al 2013a;Xue et al 2014), the golden hamster (Karsten et al 2005), and the common hamster (Banaszek et al 2012;Neumann et al 2005). Similarly, the genetic diversity of the striped hamster has experienced a trend of continuous decline in recent years.…”
Section: Genetic Diversity and Genetic Differentiationsupporting
confidence: 92%
“…In reality, these non-monotonic functions can be shown in smooth curves. bottlenecks at low density may slow down population recovery (Dong et al, 2010;Xu et al, 2013).…”
Section: Non-monotonicity Within Speciesmentioning
confidence: 99%
“…Some previous studies have focused on the effects of several main factors on dispersal, such as population density [9] [13] and sex [14] , [15] . Changes in population densities lead to the changes in the social and competitive environment over time and will eventually cause dispersal.…”
Section: Introductionmentioning
confidence: 99%
“…The dispersal rates change as the density of the population change. Specifically, empirical and demographical data provided the evidence that negative density-dependent dispersal is prevalent in voles [9] [11] , while positive density-dependent dispersal is proposed in rodents [12] , [13] . In particular groups of animals, the propensity to disperse has sex bias with different dispersal rates between males and females.…”
Section: Introductionmentioning
confidence: 99%